Immigration to Israel today: the Aliyah and its contemporary significance - Stern W, Claudia (Cuadernos Judaicos, 2012)
This article is based on a master-thesis investigation presented in june 2008 to The Shirley and Leslie Porter School for Cultural Studies at the Tel Aviv University. The main focus of this investigation was the development of young people throughout their process of immigration to Israel, and how they perceive their new reality. The core of this research is the testimony of nine young-adults, between the ages of 20 and 35, who immigrated to Israel from Argentina and Chile throughout the year 2005. The data was collected by means of in-depth interviews which took place in the year 2007. The research has a two-fold approach for analysis. The first revolves around pre-migratory surroundings, perceptions and expectations, as well as the reasons and motivations which prompted the decision to immigrate to Israel. The second pan of the analysis revolves around the post-migratory process, the development of the objects in this new culture, more global and more engaging environment, how they perceive it, and how they see themselves once in Israel. Conclusions and hypotheses follow this analysis.